Family management from Islamic perspective: an application of quality function deployment and analytic hierarchy process - Islam, Rafikul; Islam, Muhummad Khairul (2009)

(untitled)
Today, Muslim society is embroiled with many problems and there are reasons for these. It is the view of many Muslim scholars that presently the Islamic family institution is not as strong as it is supposed to be. The objective of the present research is to apply Quality Function Deployment (QFD) and Analytic Hierarchy Process (AHP) to strengthen Islamic family institution. According to the QFD framework, two types of information are required: ‘whats’ and ‘hows’; ‘whats’ are the requirements for having a strong Islamic family institution and ‘hows’ are the ways to fulfill those requirements. Data are collected from 40 Muslim scholars on a personal contact basis. AHP has been applied to prioritize the requirements (‘whats’). The QFD exercise provides the prioritized ‘technical’ requirements (‘hows’). The findings are expected to provide guidelines for having a strong family institution that can contribute towards developing a healthy society.